2019
DOI: 10.1186/s13049-019-0610-x
|View full text |Cite
|
Sign up to set email alerts
|

Key performance indicators for pre hospital emergency Anaesthesia - a suggested approach for implementation

Abstract: Background Pre-hospital Emergency Anaesthesia (PHEA) is regarded as one of the highest risk interventions that pre-hospital providers perform. AAGBI guidance from 2017 suggests the use of Key Performance Indicators (KPIs) to audit PHEA quality. The aim of this study was to develop KPIs for use in our service and evaluate their impact. Methods Using the AAGBI 2017 document as a guide we developed a list of ten auditable domains. Data for each case was extracted from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…For example, Iran’s emergency organization has introduced 16 indicators at the national level and 13 indicators at the university level, to evaluate the performance of PEC [ 53 ]. Various studies conducted in other countries are limited to developing general indicators, and specific indicators in the field of traffic accidents were less considered [ 25 , 33 , 54 ]. It should be noted that the aim of this study was not to develop a separate set and analysis system for RTIs indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Iran’s emergency organization has introduced 16 indicators at the national level and 13 indicators at the university level, to evaluate the performance of PEC [ 53 ]. Various studies conducted in other countries are limited to developing general indicators, and specific indicators in the field of traffic accidents were less considered [ 25 , 33 , 54 ]. It should be noted that the aim of this study was not to develop a separate set and analysis system for RTIs indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Through a scoping review study, Howard et al (2018) investigated the characteristics and development methods of the QIs in the field of PEC, who identified 331 QIs by the article review and 15 by the website review [29]. Similarly, there are several published studies [25,[30][31][32][33] that develop indicators for measuring the performance of PEC.…”
Section: Introductionmentioning
confidence: 99%
“…TVAA introduced CPIs for Pre‐Hospital Emergency Anaesthesia (PHEA) in March 2017 following recommendations in the AAGBI document “Safer pre‐hospital anaesthesia 2017.” Following the success of this process, it was decided to develop performance indicators for pre‐hospital blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Thames Valley Air Ambulance (TVAA) has been using CPIs for Pre‐Hospital Emergency Anaesthesia (PHEA) since early 2017 and subsequently has seen improvements in record keeping, guideline compliance, identification of equipment issues and engagement with the governance process. The introduction of CPIs for pre‐hospital blood transfusion was a logical next step.…”
Section: Introductionmentioning
confidence: 99%
“…Key performance indicators (KPIs) serve as a way of gently guiding clinicians in the right direction to improve clinical practice and is being used in different fields of medicine [5][6][7]. Santana et al [8] identified nine measurements that KPIs should meet.…”
Section: Governance Of Training Programs In Scfhsmentioning
confidence: 99%